2017
DOI: 10.1038/s41598-017-02745-6
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative and anesthesia-related cardiac arrests in geriatric patients: a systematic review using meta-regression analysis

Abstract: The worldwide population is aging, and the number of surgeries performed in geriatric patients is increasing. This systematic review evaluated anesthetic procedures to assess global data on perioperative and anesthesia-related cardiac arrest (CA) rates in geriatric surgical patients. Available data on perioperative and anesthesia-related CA rates over time and by the country’s Human Development Index (HDI) were evaluated by meta-regression, and a pooled analysis of proportions was used to compare perioperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
1
19
0
1
Order By: Relevance
“…The number of lymph nodes identified is slightly reduced in delayed ALND patients without clinical significance and the risk of lymphedema is similar between delayed and immediate ALND [29,30]. The major risk from delayed ALND for FNSN patients comes from perioperative and anesthesiarelated distress, especially in elderly patients [31,32]. In present study, two patients had metastasis in SNs and non-sentinel ALNs.…”
Section: Discussionsupporting
confidence: 44%
“…The number of lymph nodes identified is slightly reduced in delayed ALND patients without clinical significance and the risk of lymphedema is similar between delayed and immediate ALND [29,30]. The major risk from delayed ALND for FNSN patients comes from perioperative and anesthesiarelated distress, especially in elderly patients [31,32]. In present study, two patients had metastasis in SNs and non-sentinel ALNs.…”
Section: Discussionsupporting
confidence: 44%
“…20 , 36 Upon comparing in the same setting, it was observed that elderly patient was a predictor of death after emergency surgery, as that factor increased the rate by 2.8–4.3 times. 30 As for other studies such as those conducted in the USA, 4 , 11 , 27 , 34 the UK, 37 and Brazil, 38 they showed that elderly patient was a factor contributing to cardiac arrest during anesthesia, especially for patients who were more than 80 years of age. However, those studies had differences with regard to some characteristics of the population selected for entry, such as characteristic data, comorbidity disease, and surgery procedure.…”
Section: Discussionmentioning
confidence: 62%
“…Total PO mortality (commonly considered as "death from any cause and cardiac arrest (CA)) has also interest in this field. Globally, there is strong evidence of reduction in anesthetic-related and perioperative mortality over the past 50 years, despite the increasing patients ASA risks (Table 2) and decreasing of CA in the perioperative setting (Braghiroli et al 2017). Developing countries are affected two or three times more by anesthetic-related and perioperative mortality, if compared with developed countries (Avidan and Kheterpal 2012).…”
Section: Introductionmentioning
confidence: 99%